2019
DOI: 10.3389/fpsyt.2019.00722
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Regulation Among Adolescents With Pediatric Depression As a Function of Anxiety Comorbidity

Abstract: Background: Both depression and anxiety (two of the most common internalizing psychopathologies among youths) are associated with difficulties in emotion regulation (ER). Little is known about whether anxiety as a comorbid condition has an effect on the habitual use of different ER strategies in youngsters with depression histories. We aimed 1) to compare ER in adolescents with histories of childhood onset major depressive disorder (MDD) with and without comorbid anxiety and 2) to examine whether certain ER re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Extensive discussions on the concept and its development across the lifespan exist (Campos et al, 2004; Gross & Munoz, 1995; Gross & Thompson, 2007; Yap et al, 2007). Emotion regulation plays an important role in determining healthy functioning or well-being in both women and men (Dochnal et al, 2019; Ifeagwazi et al, 2019; Sekwena & Fontaine, 2018; Velotti et al, 2016).…”
mentioning
confidence: 99%
“…Extensive discussions on the concept and its development across the lifespan exist (Campos et al, 2004; Gross & Munoz, 1995; Gross & Thompson, 2007; Yap et al, 2007). Emotion regulation plays an important role in determining healthy functioning or well-being in both women and men (Dochnal et al, 2019; Ifeagwazi et al, 2019; Sekwena & Fontaine, 2018; Velotti et al, 2016).…”
mentioning
confidence: 99%
“…Teenagers need to minimize the depression symptoms with adaptive emotion regulation to pass adolescence which is full of intense emotional turmoil (Dochnal et al, 2019;Lathren et al, 2019;Wahyuni & Arsita, 2019). When intense negative emotion is experienced by teenagers without any settlement, it can slow the progress in their life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concurrent presence of a depressive disorder with prominent anxiety symptoms or an anxiety disorder is common in clinical practice. Studies have shown that more than 70% of people with depressive disorders also have anxiety symptoms (Dochnal et al, 2019;Schafer, Naumann, Holmes, Tuschen-Caffier, & Samson, 2017). Models have been proposed that explain the high correlation between the two: the first model states that they form part of a continuum because both disorders are related in mood; the second model states that the differences between the two disorders are qualitative, since orthogonal factors indicating anxiety and depression have been observed, which only show significant differences if appropriate statistical tests are used; and the third model suggests the coexistence of both syndromes in a group of so-called atypical patients, who tend to show a more chronic course of the disease, compared to depressive patients without anxiety, who tend to show a more chronic course of the disease, compared to depressive patients without anxiety (Adams, Wrath, Mondal, & Asmundson, 2018).…”
Section: Samplementioning
confidence: 99%